AAV-HBV mouse model replicates the intrahepatic immune landscape of chronic HBV patients at single-cell level - Conceição-Neto, Nádia; Pierson, Wim; Han, Qinglin; Yao, Zhiyuan; Wu, Qun; Dockx, Koen; Aerts, Liese; De Maeyer, Dries; Beyens, Matthias; Berge, Koen Van den; Li, Chris; Kukolj, George; et al. (Frontiers in Immunology, 2025)
IntroductionUnresolved hepatitis B virus (HBV) infection leads to a progressive state of HBV-specific immune dysfunctionality that characterizes chronic infection. The immune-competent adeno associated virus (AAV)-HBV mouse model is commonly used preclinically, though a comprehensive characterization of the liver immune microenvironment and its translatability to human infection is still lacking. We investigated the intrahepatic immune profile of the AAV-HBV mouse model at a single-cell level and compared with data from CHB patients in immune tolerant (IT) and immune active (IA) clinical stages.MethodsImmune exhaustion was profiled through an iterative subclustering approach for cell-typing analyses of single-cell RNA-sequencing data in CHB donors and compared to the AAV-HBV mouse model 4-weeks and 24-weeks post-transduction to assess its translatability. This was confirmed using an exhaustion flow cytometry panel at 4 and 42-weeks post-transduction.ResultsUsing single-cell RNA-sequencing, CD8 pre-exhausted T-cells with self-renewing capacity (TCF7+), and terminally exhausted CD8 T-cells (TCF7-) were detected in the AAV-HBV model. These terminally exhausted CD8 T-cells (expressing Pdcd1, Tox, Lag3, Tigit) were significantly enriched versus control mice and independently identified through flow cytometry. Importantly, comparison to CHB human data showed a similar exhausted CD8 T-cell population in IT and IA donors, but not in uninfected individuals. DiscussionLong term high titer AAV-HBV mouse liver transduction led to T-cell exhaustion, as evidenced by expression of conventional immune checkpoint markers at mRNA and protein levels. In both IT and IA donors, a similar CD8 exhausted T-cell population was identified, with increased frequency observed in IA donors. These data support the use of the AAV-HBV mouse model to study classical T-cell exhaustion in HBV infection and the effect of immune-based therapeutic interventions.